Modelling and performance analysis of electric rice cooker - Ahamed, Raju; Rashid, Muhammad Mahbubur; Islam, Md. Zahidul; Ferdaus, Mohammad Meftahul; Razzak, Md. Abdur (2014)
In modern age, technology is being used for saving time, energy and power in all cases. Undoubtedly rice cooker is an example of all these. It is a combination of cocking and warming mode by which rice is cooked and kept warm. The purpose of this paper is to model an electric rice cooker with improved warming mode. Generally bacteria can grow upto55˚ temperature and the condensation of moisture occurs below 65 temperature which causes rice spoiling. So it can easily be prevented by keeping cooked rice above 65 temperature. By following this principle two warming coil of nicrom wire are added, where one is at upper parts and another is at side wall around the fiber paper. By this process a locally available rice cooker is designed which is capable of keeping rice fresh and warm for 5-7 days and saves energy from12 to 15 units per month.